High fat diet blunts stress-induced hypophagia and activation of Glp1r dorsal lateral septum neurons in male but not in female mice - Michelle B. Bales; Samuel W. Centanni; Joseph R. Luchsinger; Payam Fathi; Jessica E. Biddinger; Thao D.V. Le; Kaitlyn Ginika Nwaba; Isabella M. Paldrmic; Danny G. Winder; Julio E. Ayala (Elsevier, 2022)
Objective: While stress typically reduces caloric intake (hypophagia) in chow-fed rodents, presentation of palatable, high calorie substances during stress can increase caloric consumption (i.e. "comfort feeding") and promote obesity. However, little is known about how obesity itself affects feeding behavior in response to stress and the mechanisms that can influence stress-associated feeding in the context of obesity. Methods: We assessed food intake and other metabolic parameters in lean and obese male and female mice following acute restraint stress. We also measured real-time activity of glucagon-like peptide-1 (Glp1) receptor (Glp1r)-expressing neurons in the dorsal lateral septum (dLS) during stress in lean and obese mice using fiber photometry. Glp1r activation in various brain regions, including the dLS, promotes hypophagia in response to stress. Finally, we used inhibitory Designer Receptors Activated Exclusively by Designer Drugs (DREADDs) to test whether activation of Glp1r-expressing neurons in the LS is required for stress-induced hypophagia. Results: Lean male mice display the expected hypophagic response following acute restraint stress, but obese male mice are resistant to this acute stress-induced hypophagia. Glp1r-positive neurons in the dLS are robustly activated during acute restraint stress in lean but not in obese male mice. This raises the possibility that activation of dLS Glp1r neurons during restraint stress contributes to subsequent hypophagia. Supporting this, we show that chemogenetic inhibition of LS Glp1r neurons attenuates acute restraint stress hypophagia in male mice. Surprisingly, we show that both lean and obese female mice are resistant to acute restraint stress-induced hypophagia and activation of dLS Glp1r neurons. Conclusions: These results suggest that dLS Glp1r neurons contribute to the hypophagic response to acute restraint stress in male mice, but not in female mice, and that obesity disrupts this response in male mice. Broadly, these findings show sexually dimorphic mechanisms and feeding behaviors in lean vs. obese mice in response to acute stress.